Chapter La solidarietà finanziaria nel contesto dell'Unione europea - BUZZACCHI, CAMILLA (Studi e saggi, 2022)
The governance of financial resources in a solidaristic key characterises, in the present age, the national systems of European countries, but it is legitimate to ask whether the same is true at the level of the European Union system. The question must be approached with attention to the two sides of the financial phenomenon: that of revenue and that of expenditure. For both profiles, therefore, it is of interest to investigate the presence of solidaristic elements, starting from the assumption of the profound diversity between systems and therefore taking into account the possibility that the rate of financial solidarity found in the supranational system is of a lower degree than the domestic one; and that the manifestations of this solidarity may take on new and original connotations, destined to add to those traditionally applied in national contexts. The aim of this contribution is therefore to develop a reflection on the ways in which financial resources are raised and spending choices are made in the European system, in order to highlight the peculiar features of the mechanisms operating there and to make an assessment of the manifestations of solidarity that can be recognised.